Penguatan Kapasitas UMKM Tenun Ulos Melalui Edukasi dan Pendampingan Harga Pokok Produksi - Naibaho, Dameria; Simbolon, Bernadetta Anita Jerry; Simanjuntak, Darmawati; Purba, Arlina; Simatupang, Eva Malina (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2025)
This community engagement program aims to enhance the managerial capacity of ulos weavers in Parbaba District, Samosir Regency, particularly in calculating the cost of goods manufactured (COGM) and implementing systematic cost recording practices. The main issue faced by the artisans is that product pricing is still based on intuition rather than accurate cost calculations, resulting in uncertain profit margins. The program was carried out through socialization, hands-on mentoring, cost calculation simulations, and group discussions with local weavers. The results show that the main partner, Ibu Nanti Sipakkar, successfully gained a clearer understanding of cost components, including raw materials, indirect materials, direct labor, and depreciation of weaving tools. The introduction of a simple manual recording format also enabled the weavers to perform basic bookkeeping without relying on digital devices. Moreover, the activity revealed that most weavers in the area do not maintain any cost records and are heavily dependent on middlemen in determining product prices. The program significantly improved the participants’ ability to calculate production costs, understand profit margins, and plan production efficiency. For sustainability, further training is recommended on digital bookkeeping, social media–based marketing strategies, and product quality enhancement to strengthen competitiveness in broader markets.